Cellular Localisation in Placenta of Placental Type Plasminogen Activator Inhibitor - Åstedt, B; Hägerstrand, I; Lecander, I (Thrombosis and Haemostasis, 1986)
A specific plasminogen activator inhibitor is known to occur in placenta and in pregnancy plasma. Immunohistochemical methods with polyclonal and monoclonal antibodies against the inhibitor were used for its localisation in term placentas. Immunoreactive material was found in the trophoblastic epithelium. It was absent in the stroma of the chorion villi.
Keywords: Placental inhibitor; Trophoblast